Networked Entrepreneurs: How Entrepreneurs Leverage Open Source Software Communities. (April 2015) - Yetis-Larsson, Zeynep; Teigland, Robin; Dovbysh, Olga
In the contemporary economy, work is increasingly becoming freelance-based while moving online. Open source software communities are rapidly becoming arenas in which individuals identify, cocreate, and realize opportunities through shared resources and expertise. Operating in a communal setting, these individuals, who we label open entrepreneurs, work and collaborate with members of their own open source community. In this article, we investigate how networked work benefits open entrepreneurs, and in particular, we focus on how open entrepreneurs are connected to other community members and how these networks affect entrepreneurial processes. Our results suggest that through different aspects of networked work, open entrepreneurs fulfill their profit motives not only in the short term but also in the long term as their networking activities facilitate the overall functioning and sustainability of the community.